Bone health in elite Kenyan runners - Tam, N.; Santos-Concejero, J.; Tucker, R.; Lamberts, R. P.; Micklesfield, L. K. (Journal of Sports Sciences, 2018)
Impact loading in athletes participating in various sports has been positively associated with increased bone mineral density (BMD), but this has not been investigated in elite Kenyan runners. Body composition and site-specific BMD measures quantified with dual x-ray absorptiometry were measured in 15 elite male Kenyan runners and 23 apparently healthy South African males of different ethnicities. Training load and biomechanical variables associated with impact loading, such as joint stiffness, were determined in the elite Kenyan runners. Greater proximal femur (PF) BMD (g · cm-2) was higher (P = 0.001, ES = 1.24) in the elite Kenyan runners compared with the controls. Six of the 15 (40%) Kenyan runners exhibited lumbar spine (LS) Z-Scores below -2.0 SD, whereas this was not found in the apparently healthy controls. PFBMD was associated with training load (r = 0.560, P = 0.003) and ankle (r = 0.710, P = 0.004) and knee (r = 0.546, P = 0.043) joint stiffness. Elite Kenyan runners exhibit greater PFBMD than healthy controls, which is associated with higher training load and higher joint stiffness. Our results reaffirm the benefits of impact loading on BMD at a weight-bearing site, while a high prevalence of low LSBMD in the elite Kenyan runners is hypothesised to be the result of a mismatch between energy intake and high training load. Future research investigating energy availability in Kenyan runners and the possible association with musculoskeletal injury should be investigated.